“Demarcando território”: tensionamentos nas pesquisas de autoria indígena no contexto da Formação Intercultural para Educadores Indígenas (FIEI) - Mariane Dias Araújo (2019)
This work analyzes the tensions that emerge from Percursos, indigenous authorship research, developed in the context of an Intercultural Training for Indigenous Educators (Formação Intercultural para Educadores Indígenas – FIEI). The work was based on the interculturality, on the decolonial perspective, and ethnomathematics perspective which articulates Ludwig Wittgenstein’s and Michel Foucault’s theoretical notions. The participants of this research are the students of the 2014/2018 Mathematics class of FIEI, offered by Federal Minas Gerais University (Universidade Federal de Minas Gerais – UFMG), belonged to five tribes: Pataxó, Pataxó Hãhãhãe, Xakriabá, Guarani and Maxakali. It is a qualitative research which empirical material is composed by the systematization texts of the researches, banners produced for a work sample, sessions of work defense, information obtained through a survey produced by the students about their researches and interviews with some students. As method of data collection was adopted the participant observation of Percursos orientation moments; questionnaire application; audio recording of the defense’s sessions of Percursos and semi-structured interviews. On a first analysis, we take an amount of texts, and from the questionnaire answers, these texts were grouped according to the investigation focus, considering using or not mathematics and the relations that were stablished between different kinds of practices. On a second analysis level, that covered all the empiric material, oriented by the first analysis results, was possible to identify seven forms which the discourse of interculturality operates in the Percursos. After, we undertook a multimodal analysis of two Percursos, identifying the tensions that occur when seek to establish relationships between indigenous tradition and mathematical practices, one of the forms in which the discourse of interculturality operates. The Percursos point to positions of resistance assumed by students, seeking to stress the Western academic model of researching, the idea that exists one reason, a single mathematic, aiming to evidence the existence of indigenous mathematics, with their own epistemologies starting from reasons, different worldviews and spiritualities. The forms in which the discourse of interculturality operates, identified on this research, brought evidences that the Percursos are essential for promoting an intercultural education at the course, regarding social, epistemic, etic and politic project.